Age heaping and accuracy of age data collected during a community survey in the Yavatmal district, Maharashtra - Pardeshi Geeta (Indian Journal of Community Medicine, 2010)
Background: Age is an important variable in epidemiological studies and an invariable part of community-based study reports. Aims: The aim was to assess the accuracy of age data collected during community surveys. Settings and Design: A cross-sectional study was designed in rural areas of the Yavatmal district. Materials and Methods: Age data were collected by a house-to-house survey in six villages. An open-ended questionnaire was used for data collection. Statistical Analysis: Age heaping and digit preference were measured by calculating Whipple′s index and Myers′ blended index. Age Ratio Scores (ARS) and Age Accuracy Index (AAI) were also calculated. Results: Whipple′s index for the 10-year age range, i.e., those reporting age with terminal digit "0" was 386.71. Whipple′s index for the 5-year range, i.e., those reporting age with terminal digit ′0′ or ′5′ was 382.74. Myer′s blended index calculated for the study population was 41.99. AAI for the population studied was 14.71 with large differences between frequencies of males and females at certain ages. Conclusion: The age data collected in the survey were of very poor quality. There was age heaping at ages with terminal digits ′0′ and ′5′, indicating a preference in reporting such ages and 42% of the population reported ages with an incorrect final digit. Innovative methods in data collection along with measuring and minimizing errors using statistical techniques should be used to ensure the accuracy of age data which can be checked using various indices.